Universal lung epithelium DNA methylation markers for detection of lung damage in liquid biopsies. Issue 5 (3rd November 2022) - Magenheim, Judith; Rokach, Ariel; Peretz, Ayelet; Loyfer, Netanel; Cann, Gordon; Amini, Hamed; Moradi, Patriss; Nagaraju, Sudharani; Sameer, Wafa; Cohen, Assaf; Fogel, Ophir; Kuint, Rottem; et al.
Background: Circulating biomarkers for lung damage are lacking. Lung epithelium-specific DNA methylation patterns can potentially report the presence of lung-derived cell-free DNA (cfDNA) in blood, as an indication of lung cell death. Methods: We sorted human lung alveolar and bronchial epithelial cells from surgical specimens, and obtained their methylomes using whole-genome bisulfite sequencing. We developed a PCR sequencing assay determining the methylation status of 17 loci with lung-specific methylation patterns, and used it to assess lung-derived cfDNA in the plasma of healthy volunteers and patients with lung disease. Results: Loci that are uniquely unmethylated in alveolar or bronchial epithelial cells are enriched for enhancers controlling lung-specific genes. Methylation markers extracted from these methylomes revealed that normal lung cell turnover probably releases cfDNA into the air spaces, rather than to blood. People with advanced lung cancer show a massive elevation of lung cfDNA concentration in blood. Among individuals undergoing bronchoscopy, lung-derived cfDNA is observed in the plasma of those later diagnosed with lung cancer, and to a lesser extent in those diagnosed with other lung diseases. Lung cfDNA is also elevated in patients with acute exacerbation of COPD compared with patients with stable disease, and is associated with future exacerbation and mortality in these patients. Conclusions: Universal cfDNA methylation markers of normal lung epithelium allow for mutation-independent, sensitive and specific detection of lung-derived cfDNA, reporting on ongoing lung injury. Such markers can find broad utility in the study of normal and pathologic human lung dynamics. This study developed biomarkers for use in liquid biopsies using DNA methylomes of human alveolar and bronchial cells, and identified elevated lung cfDNA in lung cancer as well as in COPD, including association with future exacerbation and mortality. https://bit.ly/3qu1SUZ